DINAMIKA KELEMBAGAAN DESA KOTO INUMAN DALAM PEMBANGUNAN INFRASTRUKTUR TAHUN 2019-2020 - Maica Mirna; Zulfa Harirah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine the causes of conflicts that occur between the village head and the village consultative body and see the pattern of relationships, namely the pattern of partnership, consultation and coordination in the implementation of infrastructure development in Koto Inuman Village in 2019-2020. This study uses a qualitative research method with a descriptive type of research, which can be interpreted as a problem solving process that is investigated by describing the state of the research subject based on the facts that appear during the research which is then continued based on existing theories. The presence of the village consultative body in the village government as its function and authority is expected to be able to realize a system of checks and balances in village development planning. The pattern of parallel relations between members of the village deliberative body and the village head as regulated in laws and regulations turns out to be in its implementation colored by practices of work relations that are less harmonious and lead to conflict and manifest a tendency for the village head to dominate over the village consultative body in village development. , which leads to the patron-client theory in which the patron holds higher power than the client. In this study the village head becomes a patron or has power and the village consultative body as a client or subordinate who must accept whatever is determined and given by the village head must be obeyed and accepted by the village consultative body. This is contrary to what should be, where the village head and the village consultative body are working partners and have an equal position which is clearly stated in Law Number 14 of 2014 concerning Villages and Regional Regulation of Kuantan Singingi Regency Number 4 of 2017 concerning Management and village government article 145 paragraph 1 states that the working relationship between the village consultative body and the village government is equal and becomes a partner in the administration of village governance. The conclusion in this study is that the working relationship that should run in harmony with the pattern of partnership, consultation and coordination leads to the domination and exploitation of the village head against the village consultative body which results in disharmony in the implementation of infrastructure development in Koto Inuman Village. Keywords: conflict, relationship pattern, partnership, consultation, coordination